BUM Desa (Village-Owned Enterprises) Accessibility Analysis in Accelerating Village SDGs Achievement - Rahmawati, Emma; Faubiany, Varenna; Nababan, Febrina Elia (Jurnal Economia, 2024)
AbstractThe accessibility of BUM Desa is related to the development of BUM Desa, which is also one of the driving factors towards achieving the Village SDGs. This research aims to analyse the accessibility of BUM Desa in accelerating the achievement of Village SDGs. The research approach uses quantitative. The results showed that there is a valuable and circumstantial connection between the accessibility of BUM Desa and the development of BUM Desa. In addition, it was obtained that BUM Desa with "Basic" development status has poor accessibility (93.3%), while BUM Desa with "Developing" development status has a better level of accessibility (66.7%). Likewise, BUM Desa with "Advanced" development status has excellent accessibility (60%). The development of BUM Desa is related to the 8th Village SDGs "Equitable Village Economic Growth". To accelerate the achievement of Village SDGs Goals, interventions related to BUM Desa accessibility are needed. Keywords:Accessibility, BUM Desa, Village SDGs, Bogor Regency